Organizational aspects of nutritional support for patients in a multidisciplinary emergency hospital - V. M. Luft; A. V. Lapitsky; A. M. Sergeeva (Вестник анестезиологии и реаниматологии)
Nutritional support, which is a process of substrate provision with all the nutrients necessary for life for various  categories of patients who do not have the opportunity for proper natural nutrition, is a mandatory basic component of their intensive treatment. The practical implementation of nutritional support has two aspects: clinical and organizational. Currently, all components of the clinical aspect are well developed and tested and there are no reasons not to use them in everyday clinical practice. The least resolved and worked out in the majority of our medical institutions remains the organizational aspect, which often does not allow for the proper realization of this type of medical treatment.  The article contains the main organizational options for decision the existing problem and many years of practical experience in implementing nutritional support in a multidisciplinary emergency hospital.